Nicotine dependence and quit smoking survey among current adult male smokers in Felda Bukit Goh, Kuantan, Pahang in 2015 - Swe, Swe Latt; Mohd Rus, Razman; Ab Rahman, Jamalludin; Tin, Myo Han; Htike, Myat Phyu; Nasreen, Hashima E; Abd. Aziz, Karimah Hanim (2016)

(untitled)
The study determined the prevalence of nicotine dependence (ND) among adult male smokers and their difficulties to quit smoking. A cross-sectional study was conducted among 156 current adult male smokers aged 18 to 60 years who resided in Felda Bukit Goh at Kuantan, Malaysia in 2015. Socio-economic status, history of smoking and quitting attempt within 12 months and reasons for failing quit were explored by using a self-administered questionnaire. Level of nicotine dependence was assessed by validated Malay version of Fagerstrom Test for ND questionnaires. Stratified analysis on relationship among socio-economic status, level of ND and attempt to quit smoking was done. The prevalence of low, moderate and high nicotine dependence level were 69.9 %, 28.8 % and 1.3 % respectively. Among them 55.1% (86/156) of smokers were tried to quit smoking ranging from 1 to 30 times by self-awareness (47.7%), counselled by family members (34.9%), medical personnel (10.4%) and friends (7%). The main reasons to fail quit attempt included addiction (69.8%), uncomfortable/tension (10.5%), peer smoking/social (10.5%), feel sleepy (7.9%) and desire to eat a lot (1.3%). The smokers aged 31-40 years with secondary education, private employee, moderate monthly family income (1000-3000 RM), married person and low mean ND score were mostly (55.1%) tried to quit smoking attempt. The adult male smokers with low mean ND score (2.93) and working in private sector (68.3%) were significantly tried to quit smoking. This study explored that addiction is the main reason to quit smoking and low ND group had highest quit smoking attempts. Thus, ND level assessment should be done among the smokers before engaging in the quit smoking program to provide tailored nicotine replacement therapy (NRT) to them. Effectiveness of the tailored NRT among those with different ND level should be evaluated.